Parenting for lifelong health for young children: a randomized controlled trial of a parenting program in South Africa to prevent harsh parenting and child conduct problems - Ward, CL; Wessels, IM; Lachman, JM; Hutchings, J; Cluver, LD; Kassanjee, R; Nhapi, R; Little, F; Gardner, F (Wiley, 2019)
Background Parenting programs suitable for delivery at scale in low‐resource contexts are urgently needed. We conducted a randomized trial of Parenting for Lifelong Health (PLH) for Young Children, a low‐cost 12‐session program designed to increase positive parenting and reduce harsh parenting and conduct problems in children aged 2–9.